Peningkatkan Ketahanan Duduk Pada Anak Gangguan Spektrum Autisme (GSA) Menggunakan Art Clay (Single Subject Research di Kelas II SLB Negeri 1 Solok) - Landegawa, Vera Cecilia; Rahmahtrisilvia, Rahmahtrisilvia; Marlina, Marlina; Arnez, Gaby; Handayani, Endang Sri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study began with the existence of problems in children with autism spectrum disorder (ASD) who exhibited low sitting tolerance behavior during learning. The purpose of this study was to improve the sitting tolerance behavior of second-grade ASD children at SLB Negeri 1 Solok. The approach used was quantitative with an experimental method in the form of single subject research (SSR) design A-B, and the subject was a second-grade ASD child at SDLB. Data were collected through observation using a duration instrument and documentation. This study used visual analysis in the form of descriptive graphs. The results showed that the sitting endurance behavior of the ASD child improved after the intervention using art clay media. This was evidenced by the increase in the child’s sitting endurance duration based on the results of the data analysis.